2021
DOI: 10.15587/1729-4061.2021.242334
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of pH-shifting treatment on the solubility of pumpkin seed protein isolate

Abstract: Pumpkin seed protein is a high-quality plant protein, which has all essential amino acids for the human body and can also supply essential amino acid histidine for children. When it is introduced to food products, it needs to meet some functional properties, such as solubility, emulsifying ability, foaming ability, and so on. Among them, solubility is very important because it has a great influence on other functional properties of protein. In this study, pH-shifting treatment, which is a novel method to modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The solubility of HPC samples at pH 2, 4, and 6 significantly decreased ( p < 0.05) compared to the control. This might be because the water interaction ability of the samples might be decreased at these pH levels due to the alterations in some polar compounds, such as carboxyl and amide groups [ 43 ]. Compared to the control, pH shifting treatment at pH 8 and pH 10 slightly increased the solubility of samples by 1.31% and 0.55%, respectively, although treatments with ultrasonication process at pH 8 and pH 10 significantly ( p < 0.05) enhanced the solubility of HPC by 12.12% and 19.05%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of HPC samples at pH 2, 4, and 6 significantly decreased ( p < 0.05) compared to the control. This might be because the water interaction ability of the samples might be decreased at these pH levels due to the alterations in some polar compounds, such as carboxyl and amide groups [ 43 ]. Compared to the control, pH shifting treatment at pH 8 and pH 10 slightly increased the solubility of samples by 1.31% and 0.55%, respectively, although treatments with ultrasonication process at pH 8 and pH 10 significantly ( p < 0.05) enhanced the solubility of HPC by 12.12% and 19.05%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…SMPI pH shifted at 10 (S5) in the present study showed a better amino acid profile as compared to the amino acid profile of SMPI treated at pH 2, 4, 6, and 8. This may be attributed to the better denaturation of protein structure at pH 10 than the other pH values (Gao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Natural food components, which are presented in the form of functional powders with a wide range of applications, are now popular in food science. Among them, protein isolates obtained by pH-shifting treatment from oil crops [7], with high water holding capacity [8] and under certain conditions form gels that are soluble in various food media [9]. pH-shifting treatment is a new method of protein modification and improvement of its functional properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, protein isolates obtained by pH-shifting treatment from oil crops [7], with high water holding capacity [8] and under certain conditions form gels that are soluble in various food media [9]. pH-shifting treatment is a new method of protein modification and improvement of its functional properties [7][8][9]. Interest in the nutritional value of vetch is confirmed by studies of acid hydrolysis of vetch to obtain starch [10] and its comparison with ordinary starch [11].…”
Section: Introductionmentioning
confidence: 99%